Individualized HBIG withdrawal in an historical cohort of liver transplant recipients in Italy. (March 2023) - Viganò, R.; Lenci, I.; Carrai, P.; Volpes, R.; Martini, S.; Donato, MF.; Mazzarelli, C.; Farina, E.; Cocchis, D.; Perricone, G.; Pasulo, L.; Becchetti, C.; et al.
Abstract : Introduction: Since the advent of third-generation Nucleoside-Analogues (3-NA) characterized by strong potency and high genetic barrier, the role of long-term HBIG has been questioned to the extent that Scientific Societies suggest that HBIG should be used for a finite duration, specifically in compliant patients without Delta co-infection. The same guidance applies to historical patients. Surprisinglly, many LT centres across Europe are reluctant to change and prefer continuing with HBIG-NA long term Aim: To report the results of HBV prophylaxis according to the ELITA Guidelines in a cohort of historical liver transplant recipients. Material and methods: All consecutive adherent HBV LT recipients without HDV coinfection and in regular follow-up in 7 italian sites. Patients on Lamivudine shifted to 3 − NA before HBIG-withdrawal. A prospective observational Registry for monitoring serological and biochemical paramethers was implemented. Results: 136 patients were considered for HBIG withdrawal with 2 being excluded: one refused, the other excluded for poor-compliance. One additional patient on LAM/HBIG did not tolerate shifting from LAM to entecavir. 133 patients stopped HBIG after a median time of 7 years from LT (range 1-27). HBV-Dna at LT was positive in 63%, negative in 12% and unavailable in 25% of the cases. 100 and 56 patients have a follow up of at least 3 and 6 months with 98 (98%) and 54 (96%) currently HBsAg-ve. All patients remained HBV-DNa –ve, asymptomatic and with normal liver function tests. Assuming a maintenance dose of 1000 IU every 4 weeks, the cost saving per-patient would be of at least 4.000 Euro for each additional year. For centres who have many patients in follow-up the cost saving would be substantial. Conclusion: HBIG withdrawal in adherent HBV+/HDV- patients on lifelong 3NAs is safe and associated with HBsAg negativity in the vast majority of cases. The substantial cost-saving could cover different needs.